Karakteristik Perjanjian Jual Beli Tanah yang Belum Terdaftar Hak atas Tanah - I Gusti Bagus Andika Bagaskara; I Ketut Kasta Arya Wijaya (Warmadewa Press, 2021)
Government Regulation No. 24/1997 concerning Land Registration, the Government requires all holders of land rights to register their lands with the competent authorities, but in the community there are still unregistered lands, this phenomenon is to ensure legal certainty for holders of land, land that has not been registered must be registered from the aspect of legal risk. The purpose of this study is to reveal the characteristics of the land sale and purchase agreement whose land rights have not been registered and the legal certainty of the sale and purchase agreement whose land has not been registered. This research method uses a normative legal method with a statutory approach. The technique of collecting legal materials is done by classifying legal materials. The sources of legal materials used are primary and secondary sources of legal materials. After the data was collected, the data were analyzed using descriptive analysis. The results of the study reveal that in terms of legal risks, it is more prone to occur compared to registered land, then from a procedural aspect it will be different from registered lands where unregistered land requires accuracy so as not to cause legal problems.